Marie Antoinette Season one [videorecording (DVD)] - Roussel, Guillaume, 1980- (PBS, 2023)
Marie Antoinette is just a teenager when she leaves Austria to marry the Dauphin of France. When she arrives at Versailles, she must obey the numerous and complex rules of the French court.